Rectennas of electromagnetic power harvesting systems from the surrounding space - Alieksieiev, V.O.; Gretskih, D.V.; Gavva, D.S.; Lykhograi, V.G.; Khan, I.A. (Radiotekhnika, 2023)
Progress in the development of rectenna systems for collecting/harvesting and converting the power of electromagnetic (ЕМ) fields created by radio-electronic means of various classes and purposes into direct current (DC) are considered. The article consists of two parts, each of which highlights important aspects of this topic. The main parameters of rectennas and the mechanisms of power loss in them are considered in the first part of the article. This allows us to understand the physical and technical limitations that have to be faced in the development of effective ЕМ power harvesting systems. The second part of the article considers typical schemes of rectennas for use in various applications. Features of the technical implementation of single-band rectennas, options for minimizing their dimensions and the construction of electrically small rectennas based on metasurfaces are given. Schemes of constructions of rectenna arrays and their advantages and disadvantages are also presented. Special attention in the article is paid to multi-band and wide-band rectennas. It is noted that such rectennas can store more energy and produce higher output DC power compared to narrowband rectennas. The design features of low-power rectifiers for rectennas of EM power harvesting systems from the surrounding space are considered. It was determined that the energy characteristics of rectannas are characterized by numerous factors and there are three approaches to their improvement. The first approach is to improve the parameters of individual rectifier elements, the second is to optimize the parameters of individual rectenna elements and the third is to optimize the entire rectenna as a whole.